2011
DOI: 10.5152/eajm.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Neurotrophins: Effects of Metformin and Non-Steroidal Antiinflammatory Drug Treatment

Abstract: Objective: Metabolic syndrome (MS) presents with central obesity, impaired glucose metabolism, dyslipidemia and hypertension. Our aim was to examine the effect of metformin treatment either alone or in combination with non-steroidal anti-inflammatory drugs (NSAID) on plasma levels of nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) in patients with early stage MS (MS-es) and generalized MS (MS-ge). Materials and Methods:The study compared 35 female patients with MS-es (mean age of 43.39±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(47 reference statements)
0
7
0
3
Order By: Relevance
“…Another study showed significantly increased BDNF levels in the metformin-treated group than in both the control group and the group with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinsonism in mice (11). In a human study, nonsignificantly higher plasma BDNF levels were observed in patients with metabolic syndrome after treatment with metformin (9). It was also shown that metformin treatment ameliorated the decreased mRNA of BDNF levels in Schwann cells under conditions of hypoxia.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another study showed significantly increased BDNF levels in the metformin-treated group than in both the control group and the group with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinsonism in mice (11). In a human study, nonsignificantly higher plasma BDNF levels were observed in patients with metabolic syndrome after treatment with metformin (9). It was also shown that metformin treatment ameliorated the decreased mRNA of BDNF levels in Schwann cells under conditions of hypoxia.…”
Section: Discussionmentioning
confidence: 97%
“…A limited amount of research has shown the alteration of BDNF levels to be due to antidiabetes drug treatment in vitro, in animal models and in studies in humans (9)(10)(11)(12). In our study, we found increased BDNF levels in patients who were taking metformin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, another study found that the rate of MES was at 33% based on the IDF criteria [31]. New pathophysiological data imply that MS is a real disease and its prevalence is increasing worldwide [32]. Childhood obesity is increasing the likelihood of MES in children.…”
Section: Discussionmentioning
confidence: 99%
“…В то же время в многочисленных исследованиях подчеркивается потенциальная роль ФРН в патогенезе кардиометаболических заболеваний, таких как атеросклероз, артериальная гипертензия (АГ), сахарный диабет (СД), хроническая сердечная недостаточность (ХСН), метаболический синдром (МС), а также возможность применения нейротрофических факторов в терапии данных заболеваний [6,[15][16][17].…”
Section: Discussionunclassified